Two notes on Brazilian Myrcia (Myrtaceae) - Sobral, Marcos (Phytotaxa, 2017)
Myrcia De Candolle (1827: 46) is an American genus with about 450 species (Govaerts et al. 2017). Along the examination of some Brazilian species I spotted two unresolved names in Aulomyrcia O.Berg (1855–1856: 35), a genus presently merged in Myrcia as section Aulomyrcia (O.Berg) Grisebach (1864: 234) and recently studied by Lucas et al. (2016), and here propose the necessary taxonomic changes for them. Herbaria are cited according to Thiers (2017) and specimens are identified by herbarium numbers or barcodes; links for the images may be found in herbaria homepages available in Thiers (2017).